Assessing Saturated Porcelinite as Internal Curing Agent in Self Compacted Concrete - Abeer Abdulqadir Salih (Journal of Engineering and Sustainable Development, 2013)
Self compacted concrete (SCC) describes concrete with the ability to compact itself only by means of its own weight without the requirement of vibration. It fills all recesses reinforcement spaces and voids even its highly reinforced concrete members and flows free of segregation nearly to a level balance. This research aims to assess the fresh and hardened properties of SCC using saturated porcelinite as curing agents for the internal curing of SCC. Five mixes with different percentages of replacement of saturated porcelinite ranging from (0, 12, 16, 20, 24) % of the fine aggregate volume of the same grading, were prepared, each mix tested in a fresh state with a slump test. Then 120 concrete cubes of (100*100*100)mm for different mixes were tested for, density and compressive strength, at (7,28,60, and 90) days of water and air curing. Results show that the slump decreases as saturated porcelinite content increases, density, and compressive strength increase with increasing saturated porcelinite for all age’s . The rate of increase is (10.1-30.0) % and (8.2-25.7) % for compressive strength of cubes cured in water and air respectively. The optimum percentage of saturated porcelinite which gave higher density and compressive strength was 20%.